Avaliação da qualidade de vida dos residentes de ortopedia brasileiros - ARAÚJO, A. L. S. L. C. (2018)
Main Objective: To evaluate the quality of life of Brazilian orthopedic residents and the factors that influence it. Method: This was a descriptive, cross-sectional and quantitative study that was conducted through the self-administered questionnaire to evaluate the quality of life of Brazilian orthopedic residents. The WHOQOL-Bref Quality of Life questionnaire and a sociodemographic questionnaire prepared by the researcher were used. Results: 250 third-year orthopedic residents participated in this study. It was observed that the resident of the third year (R3) of Brazilian orthopedics is characterized by the majority of males, average 30 years old, single, without children, white, living alone, owning a car, having parents with a college or university degree, up to 6 years of training, there is no other medical specialty and has already chosen the subspecialty in orthopedics. Regarding lifestyle habits, most are not smokers, they drink, are overweight, although they practice regular physical activities. They have poor and regular sleep quality and do not use continuous use medication. In relation to study habits, they study on average 1 to 4 hours / day, study in LAPTOPS / TABLETS, use online content as a source for study, access medical-scientific database and dominate the English language. Related to work habits, most of them live in the capitals, work on medical shifts beyond the required by the medical residence, working 41 to 80 hours a week, earn financial compensation or scholarship, and evaluate its performance in the residence in 7.4 (scale of 1 to 10) and your residence service at 7.4 (scale from 1 to 10). The residence service is located in the capital and has basic library as well as weekly clinical meetings. It is observed in the study that it is distributed in three groups with different degrees of quality of life (grade different among them): grade III> grade II> grade I. The residents of the grade three group, which presented higher scores in all domains (71.7% to 81.1%), that is, presented better quality of life, most of them characterized by having already chosen the subspecialty in orthopedics, presenting excellent / good sleep quality, self-evaluating well in their performance in the medical residency and evaluate your medical residency service well. Conclusion: This study allowed the characterization of the Brazilian orthopedic resident and the Brazilian orthopedic residency services, from the perspective of the resident, and an identification of the factors that influence their quality of life.